Effects of high-monounsaturated fat diet in combination with exercise training on ketone metabolism and glycemic control in diabetic rats - Khunkhong Huchaiyaphum (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2010